Marketing margins and agricultural technology in Mozambique - Arndt, Channing; Robinson, Sherman; Jensen, Henning Tarp (Informa UK Limited, 2000)
Improvements in agricultural productivity and reductions in marketing costs in Mozambique are analysed using a computable general equilibrium (CGE) model. The model incorporates detailed marketing margins and separates household demand for marketed and home-produced goods. Individual simulations of improved agricultural technology and lower marketing margins yield welfare gains across the economy. In addition, a combined scenario reveals significant synergy effects, as gains exceed the sum of gains from the individual scenarios. Relative welfare improvements are higher for poor rural households, while factor returns increase in roughly equal proportions, an attractive feature when assessing the political feasibility of policy initiatives." -- Authors' Astract